2019
DOI: 10.1007/s40996-019-00330-7
|View full text |Cite
|
Sign up to set email alerts
|

Fresh and Hardened Properties of High Calcium Fly Ash-Based Geopolymer Matrix with High Dosage of Borax

Abstract: Your article is protected by copyright and all rights are held exclusively by Shiraz University. This e-offprint is for personal use only and shall not be self-archived in electronic repositories. If you wish to self-archive your article, please use the accepted manuscript version for posting on your own website. You may further deposit the accepted manuscript version in any repository, provided it is only made publicly available 12 months after official publication or later and provided acknowledgement is giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 30 publications
(28 reference statements)
1
4
0
Order By: Relevance
“…The decrease in strength was associated with the decrease in bulk density [30]. A similar decreasing trend in compressive strength was reported by Antoni et al [31] and Bagheri et al [22] with a higher borax dosage used in the synthesis of boroaluminosilicate geopolymers. However, these contradicted other reported works.…”
Section: Properties Of Unexposed Thin Fas and Fab Geopolymerssupporting
confidence: 81%
“…The decrease in strength was associated with the decrease in bulk density [30]. A similar decreasing trend in compressive strength was reported by Antoni et al [31] and Bagheri et al [22] with a higher borax dosage used in the synthesis of boroaluminosilicate geopolymers. However, these contradicted other reported works.…”
Section: Properties Of Unexposed Thin Fas and Fab Geopolymerssupporting
confidence: 81%
“…Drastic loss in workability is a major concern in the adoption of geopolymer for practical applications. It has been reported that high calcium content is mostly responsible for the flash setting in geopolymers [46]. However, a low calcium fly ash is utilized in this study, and therefore, the occurrence of flash set at high silica fume content might not be related to calcium.…”
Section: Effect On Workability (Flowability)mentioning
confidence: 85%
“…The main parameters affecting the fly ash geo-polymer mixtures are the content of cilium, concentrations of alkaline solutions, and curing method. In GPC, the low calcium fly ash is preferred because high calcium poses the risk of flash setting before casting the elements (Antoni et al, 2020). Thus, fly ash based geopolymer concrete depends on the amount of calcium, which enhance in overall strength, reduce permeation property, and sustainability (Ankur & Rafat, 2017).…”
Section: Introductionmentioning
confidence: 99%